Social determinants for overweight and obesity in a highly marginalized population from Comitán, Chiapas, Mexico - Marisela Vázquez-Duran; María Eugenia Jiménez-Corona; Laura Moreno-Altamirano; Enrique Octavio Graue-Hernández; Noé Guarneros; Leonardo Jiménez-Corona; Aida Jiménez-Corona (Instituto Nacional de Salud Pública, 2020)
Objective. We assessed the prevalence of overweight and obesity and its association with some social determinants in a highly marginalized population in Mexico. Materials and methods. Cross-sectional study conducted in Comitán, Chiapas, from 2010 to 2012, comprising 1 858 subjects aged ≥20 years. We evaluated proximal, intermediate, and structural social determinants. Results. The prevalence of overweight and obesity was 37.9 and 16.5%, respectively. The probability of overweight and obesity was higher in participants with ≥primary school, self-reported non-indigenous origin, and medium level of marginalization compared with those with <primary school, self-reported indigenous origin, and high/ very high level of marginalization. Conclusion. The probability of overweight and obesity was higher in population with more favorable social conditions, which may be partially explained by changes in the traditional lifestyle with greater access to high energy foods and physical inactivity.